Mindhunnur: Character Formation as a Structural Achievement in Islamic Learning - Fara Fariha Rodliyana; Nur Efendi (Al-Qalam Institute, 2026)
The management of Islamic education remains divided between the rational instruments of modern administration and the moral and spiritual commitments that define its purpose, leaving the field without a unified model in which managerial technique is governed by Islamic values. This study examines the concept of Mindhunnur, developed by Qomar, which proposes a synthesis of modern managerial rationality and Islamic moral foundations, yet has not been systematically analyzed or positioned within the wider scholarship on Islamic education management and the integration of knowledge. The objective of the study is to reconstruct the philosophical foundation of Mindhunnur, to examine its expression across the principal typologies of Islamic educational institution, and to specify the level at which it integrates managerial and Islamic knowledge. Employing a qualitative library research design adapted to a PRISMA-guided selection of Scopus-indexed sources, the study analyses the primary articulation of Mindhunnur against a contemporary corpus through content analysis and descriptive-analytical interpretation. The findings establish that Mindhunnur rests on a coherent foundation integrated at the axiological rather than the epistemological core, that its realization depends on the structural position of embodied moral leadership, and that this leadership, rather than administrative reform, is the decisive carrier of character formation. The implication is that Mindhunnur offers a framework for transformative education and learning, in which character formation becomes a structural achievement of moral leadership and a foundation for genuinely transformative institutional change.